Analysis Implementation of COVID-19 Prevention Policy for Disability in Social Institution (Case Study: Jakarta CapitalCity) (Case Study: Jakarta Capital City) - Margaretha, Cindy; Ayuningtyas, Dumilah (Kesmas, 2021)
One of the most vulnerable groups in the current COVID-19 pandemic situation is people with disabilities. Generally, people with disabilities have more health care needs, both everyday needs and needs related to the disorders/limitations. As part of human beings and citizens of Indonesia, constitutionally, people with disabilities have the same rights and position before the law and government. This study aimed to analyze the implementation of COVID-19 prevention policies at the social institutions for disability in Jakarta Capital City, provide information about the implementation, find out the obstacles, and recommend policymakers to prevent COVID-19 in social institutions with disabilities. This study used an exploratory study design with a rapid assessment survey approach, using a secondary data analysis method supported by interviewing stakeholders at the Social Institutions in Jakarta Capital City handling disabilities. The results of this study concluded that the overall implementation has been going well. The socialization and coordination process related to the COVID-19 prevention policy at the Social Institution for Disabilities in Jakarta Capital City has gone well among fellow officers but has communication barriers with residents